Perancangan UI/UX Pada Website Tinggal Order Dengan Figma Menggunakan Metode User Centered Design - Fahrullah, Haerullah; Fahrullah, Fahrullah; Rivaldy, Tico (DPPM Universitas Pelita Bangsa, 2025)
This research aims to analyse the User Interface (UI) and User Experience (UX) of the website profile shop ‘Tinggal Order’ using the User-Centered Design (UCD) method. UCD is a design approach that places the user at the centre of the entire design process, with a primary focus on user needs, preferences, and involvement. This method is used to ensure that the resulting website not only fulfils business needs but also provides an optimal user experience. This research involves the stages of identifying user needs, prototyping, and UI/UX evaluation through testing with end users. The results showed that the application of UCD was able to improve the ease of use (usability), user satisfaction, and interaction effectiveness on the ‘Tinggal Order’ website. The usability results obtained an average of 84.886, with the grade A category. This figure can be said to be very good, which means that the design made can be accepted by potential users. While the resulting prototype can help provide information to the general public about news and information about the ‘Tinggal Order’ store.